MITIGASI SAMPAH ANTARIKSA: MENINJAU KESIAPAN REGULASI NASIONAL - Shannon Suryaatmadja (Fakultas Hukum Universitas Gadjah Mada, 2020)
AbstractThe rapid development of space activities has increased the risk of space object collisions in orbit, particularly of space debris. This situation potentially harms satellites and endangers space missions. To date, international efforts generally result in non-legally binding products or soft laws, providing only guidance to form a national legal framework in mitigating space debris. This article aims to review Indonesia’s efficacy in regulating its space activities to minimize space debris generation and risks. It also examines mitigation efforts in several other countries with the intention of providing input for the current national legal framework. IntisariPesatnya perkembangan kegiatan antariksa meningkatkan risiko tabrakan antar objek antariksa pada orbit bumi, terutama sampah antariksa. Situasi ini berpotensi merusak satelit hingga membahayakan keberlangsungan misi antariksa. Hingga kini, upaya internasional baru sanggup melahirkan produk hukum tidak mengikat, sehingga hanya mampu mengarahkan negara untuk menyusun kerangka hukum nasional dengan memperhatikan perihal mitigasi sampah antariksa. Artikel ini akan mengkaji kesiapan regulasi nasional untuk meminimalkan risiko timbul dan bertambahnya sampah antariksa. Dibahas pula perbandingan upaya mitigasi pada beberapa negara lain guna memberi masukan bagi Indonesia.